2020
DOI: 10.3390/ijerph17031063
|View full text |Cite
|
Sign up to set email alerts
|

Experience as a Determinant of Declarative and Procedural Knowledge in School Football

Abstract: The study of declarative and procedural knowledge makes it possible to ascertain what cognitive processes are like during motor learning. This study aimed to compare, according to the methodology, gender and experience (football practise), and the levels of declarative and procedural knowledge after the implementation of two intervention programmes on school football including one based on the tactics learning and the other on the technique learning. A total of 41 students in the 5th year of primary education … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 40 publications
3
15
0
4
Order By: Relevance
“…Furthermore, the learners with less initial football ability improved more in their tactical awareness than did those with greater initial ability [30,48]. It can be presumed that a relatively greater amount of learning is likely to occur in invasion sports for those individuals who learn in environments that foster more active student engagement [49].…”
Section: Effect Of Previous Experiencementioning
confidence: 99%
“…Furthermore, the learners with less initial football ability improved more in their tactical awareness than did those with greater initial ability [30,48]. It can be presumed that a relatively greater amount of learning is likely to occur in invasion sports for those individuals who learn in environments that foster more active student engagement [49].…”
Section: Effect Of Previous Experiencementioning
confidence: 99%
“…García-Ceberino, Gamero, Feu, and Ibáñez [ 11 ] carried out quasi-experimental research to compare the declarative and procedural knowledge acquired by two groups of fifth-year students after implementing two intervention programs in school football: The Tactical Games Approach vs. the Direct Instruction Model. The results revealed no significant intergroup differences with regard to the methodology applied.…”
Section: The Studies Includedmentioning
confidence: 99%
“…The test analyzes knowledge of the player based on attacking and defense contextual problems at on-the-ball and off-the-ball situations. Recently, García-Ceberino et al (2020) investigated the effect of two tactical and technical interventions on declarative and procedural tactical knowledge of soccer schools' players aged between 10-11 years old with different gender and level of experience. Evaluation of tactical knowledge through STKT showed that both of interventions led to improvement of tactical knowledge of all the participants.…”
Section: Introductionmentioning
confidence: 99%